Effect Of Company Size And Profit Management On The Cost Of Equity Capital - Agus, Rosida Maedina; Mansyur, Syahrul; Amin, Asbi (Jurnal Penelitian Ekonomi Dan Akuntansi, 2024)
The aim of this research is to determine the effect of company size on the cost of equity capital, as well as to determine the effect of earnings management on the cost of equity capital. The approach used in This research is a quantitative approach. The population in this research is all manufacturing companies on the Indonesian Stock Exchange. Currently there are 63 manufacturing companies listed on the Indonesian Stock Exchange. TechniqueiiThe sampling in this research was carried out using purposive sampling, so the number of samples was 57 financial report data from 19 sample companies with an observation period of three years. The collected data was then analyzed using multiple linear regression analysis. The research results found that company size did not have a significant effectiion the cost of equity capital, while earnings management has a significant effect on the cost of equity capital. an increase in earnings management will increase the cost of equity capital.